(untitled) (Estudios Sociales, 2023)
The specialized literature on social movements and contentious politics in Argentina during the democratic transition has focused on the emergence and dynamics of particular actors, or has concentrated on certain critical junctures. But it has neglected a global vision of the social mobilization of the period, thus disassociating the emergence of these new actors from the persistent and central character of other classic actors of the mobilization processes, such as the trade unions, after the last military dictatorship. This article seeks to restore this global vision and presents a map of social protest during 1984-1989 with the aim of putting the study of social mobilization processes into perspective. We resort to the analysis of a database of protest events specially designed for this purpose.